Poetry of Compassion. On the work of Inna Lisnyanskaya - Koubatian, Georgi (Bulletin of Yerevan University H: Russian Philology, 2021)
Inna Lisnyanskaya (1928–2014) is a highly visible figure in Russian poetry of the last decades. Under the Soviets many of her poems could not be issued due to the censorship restrictions, and during 1979-1987 she was not published in the USSR at all. After 1988 Lisnyanskaya got her recognition, critical acclaim and some prestigious awards (RF State Prize, Solzjenicin Prize, the prize “Poet”). Born and raised in Baku (her mother was an Armenian), Lisnyanskaya repeatedly addressed herself to Armenian themes (massacres in Shushi in 1918 and in Baku in 1990, the destruction of “her dearest” Stepanakert in 1992). “Armenian verses" аге not exceptional, but more than natural in the trend of Lisnyanskaya's poetry. It is shown in the paper, that they reflect characteristic features of her work .
Keywords: Christian motives, compassion, personal fault, the Armenian themes